Biosynthesis of Rhizobium meliloti lipooligosaccharide Nod factors: NodA is required for an N-acyltransferase activity. - Atkinson, E M (1994)
Rhizobium bacteria synthesize N-acylated beta-1,4-N-acetylglucosamine lipooligosaccharides, called Nod factors, which act as morphogenic signal molecules to legume roots during development of nitrogen-fixing nodules. The biosynthesis of Nod factors is genetically dependent upon the nodulation (nod) genes, including the common nod genes nodABC. We used the Rhizobium meliloti NodH sulfotransferase to prepare 35S-labeled oligosaccharides which served as metabolic tracers for Nod enzyme activities. This approach provides a general method for following chitooligosaccharide modifications. We found nodAB-dependent conversion of N-acetylchitotetraose (chitotetraose) monosulfate into hydrophobic compounds which by chromatographic and chemical tests were equivalent to acylated Nod factors. Sequential incubation of labeled intermediates with Escherichia coli containing either NodA or NodB showed that NodB was required before NodA during Nod factor biosynthesis. The acylation activity was sensitive to oligosaccharide chain length, with chitotetraose serving as a better substrate than chitobiose or chitotriose. We constructed a putative Nod factor intermediate, GlcN-beta 1,4-(GlcNAc)3, by enzymatic synthesis and labeled it by NodH-mediated sulfation to create a specific metabolic probe. Acylation of this oligosaccharide required only NodA. These results confirm previous reports that NodB is an N-deacetylase and suggest that NodA is an N-acyltransferase.